2019
DOI: 10.4103/jlp.jlp_93_19
|View full text |Cite
|
Sign up to set email alerts
|

Trends of voluntary reporting of needlestick injuries and hepatitis B vaccination status among health-care workers of a tertiary health care center in Puducherry

Abstract: BACKGROUND: Health-care workers (HCWs) can sustain needlestick injuries (NSIs) during patient care activities and are at a greater risk of exposure to blood-borne infectious agents such as HBV, HCV, and HIV, among which only HBV has an effective vaccine. Unfortunately, both the voluntary reporting rates of NSIs and HBV vaccination coverage among HCWs have been generally low. This study aims to analyze the trends of voluntary reporting of NSIs and the HBV vaccination status among the HCWs of our tertiary health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The study conducted by Thiyagarajan M et al showed that nursing staffs were the most commonly reported sharp/needle stick injury (44.6%) followed by students (14.5%) and janitors (13.3%). 9 Another study by Goel V et al reported that a large number of the sharp/NSIs incidents among doctors (73.7%) followed by interns (7.4%), and faculty members (1.1%). Interestingly, only 19.1% nurses reported injuries, while 3.2% of the exposed HCWs were hospital waste disposal staff, not involved directly in patient care or surgical procedures.…”
Section: Discussionmentioning
confidence: 98%
“…The study conducted by Thiyagarajan M et al showed that nursing staffs were the most commonly reported sharp/needle stick injury (44.6%) followed by students (14.5%) and janitors (13.3%). 9 Another study by Goel V et al reported that a large number of the sharp/NSIs incidents among doctors (73.7%) followed by interns (7.4%), and faculty members (1.1%). Interestingly, only 19.1% nurses reported injuries, while 3.2% of the exposed HCWs were hospital waste disposal staff, not involved directly in patient care or surgical procedures.…”
Section: Discussionmentioning
confidence: 98%
“…Due to contact of non-intact skin or mucous membranes with tears, saliva or blood containing HBVinfected secretions or through sharing of toothbrushes horizontal transmission occurs. 14 There is even chance that patients remain asymptomatic for years and unknowingly may transmit the infection to others via perinatally, percutaneously, sexually , or through close person-to-person contact (e.g., open cuts and sores). 4…”
Section: Risk Factorsmentioning
confidence: 99%
“…Out of 35 million health-care workers (HCWs) around 2million sustain NSIs every year, as a result of which they are at risk of exposure to blood-borne infectious agents including HBV. 14 Through NSIs risk of transmission of HBV is (6%-30%). 5,14 As compared to adult general population, HCWs are four fold more at risk of acquiring the Hepatitis B infection.…”
Section: Health Care Workers (Hcw)mentioning
confidence: 99%
See 2 more Smart Citations